Question: what is the better way to simplificar the equation?

Anteriorly, I had done a question that you answered in the forum and it basically it was about the simplification of a equation. I'm posting the print of the screen and the code because the question of today is similarly, but not completely, because there are something that make more complicate the code that I devolved.

restart;
Hi := -Delta*S1^2 - J*S1*S2;
R1 := S1*exp(-beta*Hi);
R1 := add(R1, S1 = [--1, 0, 1]);
R2 := exp(-beta*Hi);
R2 := add(R2, S1 = [-1, 0, 1]);
S := R1/R2;
S := convert(S, trig, {J*S2});
S := simplify(S);
S := convert(S, exp, {Delta});

and

In this case I had to put in evidence the therm exp(Delta beta), where I simplified the expression. Now, we have more 2 variables (+2 and -2) to substitute in the equation. The code is:

restart;
Hi := -Delta*S1^2 - J*S1*S2;
R1 := S1*exp(-beta*Hi);
R1 := add(R1, S1 = [-2, -1, 0, 1, 2]);
R2 := exp(-beta*Hi);
R2 := add(R2, S1 = [-2, -1, 0, 1, -2]);
S := R1/R2;
S := convert(S, trig, {J*S2});
S := simplify(S);
S := convert(S, exp, {Delta});

In the last line we had the final equation

What should I change in the code for that my exponential function continue in evidence? This is, for my expression  be

(4*sinh(2*J*S2*beta) + 2*sinh(J*S2*beta)*exp(-3*Delta*beta))/(2*cosh(2*J*S2*beta) + 2*cosh(J*S2*beta)*exp(-3*Delta*beta) + exp(-4*Delta*beta))

Please Wait...